Z dokazi podprta rehabilitacija bolnikov po nihajni poškodbi vratu - Marn-Vukadinović, Duša (Rehabilitacija (Ljubljana), 2011)
Whiplash-associated disorders (WAD) are a frequent public health problem. A large proportion of patients develop chronic WAD with significant disability-related expenses, social, economic and legal services costs. Effective therapies to prevent chronicity are essential. The present article shows commonly used noninvasive interventions during acute, subacute and chronic WAD. The evidence based effectiveness of these rehabilitative treatments is listed according to their influence on impairment, activity and participation of patients after WAD considering environmental and personal factors, too.
Keywords: efficiency; metode; poškodbe; rehabilitacija; učinkovitost; vocational rehabilitation; vrat; Vrata